Knowledge and Use of Mouthguards among University Athletes in Malaysia - Abdullah, D.; Wee, C.L.F.; Ahmad, W.A.W.; Robin, R.; Peen, T.S.; Khoo, S. (Innovative Manufacturing, Mechatronics & Sports Lab (iMAMS), 2013)
Participation in contact sports has been shown to carry a considerable risk of sustaining dental injuries. It is important for athletes to use available preventive gear to protect themselves from these injuries. Aim of the study: To assess the knowledge, habit and preferences of using mouthguards among university athletes. Materials and Method: Self-administered questionnaires, consisting of Part A - Age, gender, type of sporting activities, total hours dedicated to sports training, level of sports representation; Part B - Awareness of risk of dental injuries, knowledge on mouthguards such as definition of a mouthguard, role of mouthguard, use of mouthguards and reasons for not wearing mouthguards; and Part C – Experience of sustaining dental injuries during sports activities, were distributed. Athletes who were university students over 18 years and under 30 years of age and athletes who claimed to know about mouthguards were included in the study. Results: Data of a total of 225 respondents were analysed, consisting of 68% (n=154) male and 32% female (n=71) with the mean age of 21 years old. Only 46% (n=104) knew exactly about mouthguards and its role in the prevention of dental injuries during sports. Thirty seven percent of them (n=84) have used mouthguards and they were mostly in the martial arts group. The mouthguards were usually provided by the management team (62%). Forty percent of the respondents (n=91) claimed to have sustained dental injuries while playing sports and the injuries occurred more frequently in hockey (65.3%), basketball (60%) and soccer (45.2%). Conclusions: The incidence of dental trauma in contact sports shows that the awareness and use of mouthguards must be intensified. Awareness campaigns focusing on dental trauma should be organized to improve the knowledge of athletes.